Understanding to Intergroup Conflict: Social Harmonization and Law Awareness of Society - Syahruddin Nawi; Muhammad Syarif; Aswad Rachmat Hambali; Salle Salle (Susbtantive Justice International Journal of Law, 2019)
The development and progress of the city of Makassar in line with the occurrence of disturbing conflicts, conflicts and even war between groups provide an overview of research problems regarding the erosion of nationalism, erosion of national ideology, low national character, erosion of local culture, shallow religious values, low sense of solidarity, moral decline , and ethnic fanaticism and declining character quality and declining character quality, all of which have the potential to threaten National Integration and Social Harmony. This research method is descriptive and form of presentation in a systematic, factual and accurate description of the facts obtained. The results showed that conflict/war between groups or residents still occurred in at least six 6 regions in Makassar that had caused various losses because war between groups or residents involved children or adolescents using dangerous objects. There are 30 factors, namely juvenile delinquency, multi aspects, peaceful disturbance, offensive, revenge, social, economic, jealousy, work area disputes, unemployment, ethnicity, religion, culture, wild race, women, competition, misunderstanding, social change, deprivation land, women who seize men (infidelity of women), youth group clashes, politics/parties, deception, social classes/strata, selfishness, arrogance, ridicule, slander, conflict of interest, and government land disputes. Recommendations are needed Conflict Resolution Forum (FOLEKO) as a preventive and repressive measure, provide guidance and counseling for members of the community, about legal awareness, social ethics and courtesy in family life and community life, and inculcation of religious values ​​and national integrity, the authorities need to be more intensive in conducting surveillance and need to carry out routine checks on the possession of dangerous sharp objects, and it is necessary to have the Social Harmony Creation Model module and legal awareness as recommendations of this research.